The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1177/0149206315598372
|View full text |Cite
|
Sign up to set email alerts
|

What Is Wrong With Treating Followers Differently? The Basis of Leader–Member Exchange Differentiation Matters

Abstract: In this paper, we identify the basis of leader-member exchange (LMX) differentiation as a crucial factor influencing the relationship between LMX differentiation and work group outcomes. Drawing from the relational theories of procedural justice, we theorize members' task performance and organizational citizenship behavior (OCB) as the two main bases of LMX differentiation. We hypothesize that LMX differentiation will be less negatively related to intragroup relational quality and group proactivity when there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 95 publications
(199 reference statements)
7
97
0
Order By: Relevance
“…Second, scholars have focused on LMX differentiation in teams, which describes the extent to which team members have different levels of exchange with their leaders. Chen, He, and Weng () found that LMX differentiation had a negative impact on team proactive behavior, but this effect became weaker when the differentiation was based more on individuals' task performance and organizational citizenship behavior. Third, the effect of exchange relationships with higher level leaders have been examined.…”
Section: Social Context Factors As Antecedents Of Proactive Behaviormentioning
confidence: 99%
“…Second, scholars have focused on LMX differentiation in teams, which describes the extent to which team members have different levels of exchange with their leaders. Chen, He, and Weng () found that LMX differentiation had a negative impact on team proactive behavior, but this effect became weaker when the differentiation was based more on individuals' task performance and organizational citizenship behavior. Third, the effect of exchange relationships with higher level leaders have been examined.…”
Section: Social Context Factors As Antecedents Of Proactive Behaviormentioning
confidence: 99%
“…Low LMX variation involves equal treatment of followers, which could occur regardless of relative contribution, and thus fulfils the norm of equality and contravenes the norm of equity. Empirical studies examining both cognitive and affective group states (e.g., Chen, He, & Weng, ; Cobb & Lau, ; Li & Liao, ) have reported moderate negative correlations between LMX variation and processes such as group cohesion, group proactivity, coordination, and communication. A particularly noteworthy study is that of Li and Liao () which was longitudinal in design and collected objective outcomes of performance (reported as team profit).…”
Section: Theoretical Approaches and Empirical Findingsmentioning
confidence: 99%
“…Of particular interest was that LMX variation had a negative effect on climate strength, meaning it reduced the consistency of justice perceptions (more than the level or average climate perceptions). Examining both justice and conflict, Chen et al () found that LMX differentiation was more harmful when the grounds for differentiating amongst team members were not considered “fair” (i.e., team members' task performance was not the main basis for leaders' differentiation processes).…”
Section: Theoretical Approaches and Empirical Findingsmentioning
confidence: 99%
“…The idea of differentiated leadership was first elaborated in the leader-member exchange (LMX) literature (Chen, He, and Weng 2015;Erdogan and Bauer 2010;Liden et al 2006), and was later extended to research in transformational leadership (Cole and Bedeian 2007;Cole et al 2011;Wu et al 2010). Wu and colleagues (2010) defined differentiated leadership as "the case in which a leader exhibits varying levels of individual-focused leadership behavior to different group members" (p. 90).…”
Section: Differentiated Empowering Leadership and Followers' Trust Inmentioning
confidence: 99%